Functional insights of an uncommon hypomorphic variant in IL2RG as a monogenic cause of CVID-like disease with antibody deficiency and T CD4 lymphopenia - González-Torbay, Andrea; Reche-Yebra, Keren; Clemente-Bernal, Álvaro; Serrano, Yolanda Soto; Bravo-Gallego, Luz Yadira; Fernández López, Almudena; Rodríguez-Pena, Rebeca; García-Morato, María Bravo; López-Granados, Eduardo; del Pino-Molina, Lucía (Frontiers in Immunology, 2025)
BackgroundOver the last decade, the identification of hypomorphic variants in patients previously diagnosed with Common Variable Immunodeficiency (CVID) has led to the association of milder phenotypes with variants of the IL2RG gene that are usually related to severe combined immunodeficiency. Indeed, several revertant mosaicisms have been described in cases with hypomorphic variants in that gene. Our main objective herein was the functional characterization of p. (Pro58Thr) variant in the IL2RG gene in an adult patient with antibody deficiency and moderate CD4+ T cell lymphopenia.MethodsEvaluation of the patient included a clinical examination and a complete analysis of the peripheral blood phenotype. To further explore IL2RG functionality we selected downstream signaling readouts, namely STAT3 and STAT5 phosphorylation, NK degranulation and B- and T-cell proliferation capacity in vitro, which can be measured by flow cytometry, that reflect the strength of homeostatic signaling pathways in resting cells and after activation.ResultsThe patient presented reduced CD132 expression and conserved T- and B-cell proliferation capacity in vitro. However, we found that intracellular signaling downstream of IL2γc is affected, with reduced STAT3 phosphorylation after IL-21 stimulation in B cells and CD4 T cells. In addition, CD4+ T cells showed a reduced STAT5 phosphorylation in response to IL-2, which was not so evident in CD8+ T cells. NK degranulation was impaired upon PHA and IL-2 as well as plasmablast differentiation in vitro.ConclusionWe conclude that p. (Pro58Thr) in the IL2RG gene is functionally a hypomorphic variant, as reported previously. Although the functionality of CD8+ is less impaired than the rest of the lymphocyte subsets, we did not detect a reversion of the variant in isolated CD8+, CD4+, CD19+ or NK cells.